Room-temperature mechanocaloric effects in lithium-based superionic materials - Arun K. Sagotra (Nature Portfolio, 2018)
Large mechanocaloric effects are disclosed in lithium-ion superionic conductors at room temperature. These occur in the absence of any structural phase transition, which is beneficial from a practical point of view, and are related to stress-induced variations in the ionic conductivity.